Healthcare workers: occupational carcinogenic factors and cancer risk - L. G. Solenova; L. A. Nekrasova (Успехи молекулярной онкологии)
The number of healthcare workers is over two million in Russia. Many of them are exposed to hazardous physical, chemical and biological occupational factors acting along with psychological strain. The results of large epidemiological studies carried out in various countries revealed greater cancer risk in physicians and nurses: cancer of the breast, skin, brain and other sites. Higher cancer risk of lung, breast, uterine, ovary, brain is considered to be associated with ionizing radiation. The female healthcare workers who handle antineoplastic drugs showed a greater risk of birth defects in offspring, spontaneous abortions and breast cancer. In Russia, the growing number of accidents among healthcare workers following transmission of infection by carcinogenic biological factors such as HBV and HIV is observed. Higher risk of reproductive impairments, hyperplasia of the breast and uterine tissues, breast cancer are revealed in nurses working the night shift. In Russia, there is lack of epidemiological studies of cancer risk among healthcare workers, the number of medical personal exposed to occupational carcinogens is unknown. That all does not show the actual situation in our country and does not allow setting priorities in cancer prevention among medical workers.